Bacterial succession on decomposing leaf litter exhibits a specific occurrence pattern of cellulolytic taxa and potential decomposers of fungal mycelia - Tláskal, Vojtěch; Voříšková, Jana; Baldrian, Petr (FEMS microbiology ecology, 2016)
The decomposition of dead plant biomass contributes to the carbon cycle and is one of the key processes in temperate forests. While fungi in litter decomposition drive the chemical changes occurring in litter, the bacterial community appears to be important as well, especially later in the decomposition process when its abundance increases. In this paper, we describe the bacterial community composition in live Quercus petraea leaves and during the subsequent two years of litter decomposition. Members of the classes Alpha-, Beta- and Gammaproteobacteria and the phyla Actinobacteria, Bacteroidetes and Acidobacteria were dominant throughout the experiment. Bacteria present in the oak phyllosphere were rapidly replaced by other taxa after leaf senescence. There were dynamic successive changes in community composition, in which the early-stage (months 2-4), mid-stage (months 6-8) and late-stage (months 10-24) decomposer communities could be distinguished, and the diversity increased with time. Bacteria associated with dead fungal mycelium were important during initial decomposition, with sequence relative abundances of up to 40% of the total bacterial community in months 2 and 4 when the highest fungal biomass was observed. Cellulose-decomposing bacteria were less frequent, with abundance ranging from 4% to 15%. The bacterial community dynamics reflects changes in the availability of possible resources either of the plant or microbial origin.
Keywords: Forests; houby; listy rostlin; Biomass; lesy; koloběh uhlíku; Microbiota; Plant Leaves; dub (rod); půdní mikrobiologie; Quercus; Fungi; mikrobiota; celulosa; Mycelium; mycelium; Bacteria; Soil Microbiology; biomasa; Cellulose; Carbon Cycle